Selection for longer lived sperm within ejaculate reduces reproductive ageing in offspring. Issue 2 (1st April 2019) - Alavioon, Ghazal; Cabrera Garcia, Andrea; LeChatelier, Magali; Maklakov, Alexei A.; Immler, Simone
Abstract: Males produce numerous sperm in a single ejaculate that greatly outnumber their potential egg targets. Recent studies found that phenotypic and genotypic variation among sperm in a single ejaculate of a male affects the fitness and performance of the resulting offspring. Specifically, within-ejaculate sperm selection for sperm longevity increased the performance of the resulting offspring in several key life-history traits in early life. Because increased early-life reproductive performance often correlates with rapid ageing, it is possible that within-ejaculate sperm selection increases early-life fitness at the cost of accelerated senescence. Alternatively, within-ejaculate sperm selection could improve offspring quality throughout the life cycle, including reduced age-specific deterioration. We tested the two alternative hypotheses in an experimental setup using zebrafish Danio rerio . We found that within-ejaculate sperm selection for sperm longevity reduced age-specific deterioration of fecundity and offspring survival but had no effect on fertilization success in males. Remarkably, we found an opposing effect of within-ejaculate sperm selection on female fecundity, where selection for sperm longevity resulted in increased early-life performance followed by a slow decline, while females sired by unselected sperm started low but increased their fecundity with age. Intriguingly, within-ejaculate sperm selection also reduced the age-specific decline in fertilization success in females, suggesting that selection for sperm longevity improves at least some aspects of female reproductive ageing. These results demonstrate that within-ejaculate variation in sperm phenotype contributes to individual variation in animal life histories in the two sexes and may have important implications for assisted fertilization programs in livestock and humans.